2023
DOI: 10.30773/pi.2022.0307
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Disorders and Associated Factors in Korean Adults: National Mental Health Survey of Korea 2021

Abstract: Objective Mental health is a global concern and needs to be studied more closely. We aimed to estimate the prevalence of mental disorders and their associated factors among the general population in Korea.Methods The National Mental Health Survey of Korea 2021 was conducted between June 19 and August 31, 2021 and included 13,530 households; 5,511 participants completed the interview (response rate: 40.7%). The lifetime and 12-month diagnosis rates of mental disorders were made using the Korean version of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…This study could not confirm the diagnostic accuracy through retrospective medical record reviews that are used in studies using claims data because patient consent is required for medical record review. However, in previous studies of Korea that investigated the diagnostic consistency between the NHICD and electronic medical record, psychiatric illness was higher than for other diseases and highly sensitive of disease because of stigma against psychiatric illness in Korea . Second, important factors that may affect suicide risk, such as social support, history of suicide attempts, and socioeconomic status, were not considered as potential covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study could not confirm the diagnostic accuracy through retrospective medical record reviews that are used in studies using claims data because patient consent is required for medical record review. However, in previous studies of Korea that investigated the diagnostic consistency between the NHICD and electronic medical record, psychiatric illness was higher than for other diseases and highly sensitive of disease because of stigma against psychiatric illness in Korea . Second, important factors that may affect suicide risk, such as social support, history of suicide attempts, and socioeconomic status, were not considered as potential covariates.…”
Section: Discussionmentioning
confidence: 99%
“…However, in previous studies of Korea that investigated the diagnostic consistency between the NHICD and electronic medical record, psychiatric illness was higher than for other diseases 29 and highly sensitive of disease because of stigma against psychiatric illness in Korea. 30 Second, important factors that may affect suicide risk, such as social support, history of suicide attempts, and socioeconomic status, were not considered as potential covariates. However, this information is not available because the NHICD is collected for reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…A sampling method based on catchment areas was used in 2011, but the 2021 survey sampled the entire areas of Korea. The details of the 2011 and 2021 surveys have already been provided [14,15]. A total of 6,022 and 5,511 participants were included in the 2011 and 2021 surveys, respectively (response rates of 78.7% and 43.8%).…”
Section: Data Collectionmentioning
confidence: 99%
“…Data from South Korea’s National Health Insurance System indicated that in 2021, approximately 3.1% of the nation’s total population was receiving treatment for anxiety disorders. Although 580,000 people are undergoing treatment in Korea, the actual number of people suffering from anxiety disorders is estimated to be approximately four to five times higher [ 2 ]. A systematic review estimated the economic burden of anxiety disorders to range from 0.25 to 0.78% of a country’s GDP [ 3 ].…”
Section: Introductionmentioning
confidence: 99%